Prevalence, sociodemographic risk factors, and coverage of myopia correction among adolescent students in the central region of Portugal - Amélia Fernandes Nunes; Mariana Cunha; Miguel Castelo-Branco Sousa; Cristina Albuquerque Godinho (BMC, 2024)
Abstract Background Knowing the prevalence of myopia at school age is essential to implement preventive measures and appropriate interventions, ensure access to vision care, promote a healthier educational environment and improve academic performance. The purpose of this study was to determine the prevalence of myopia and its associated sociodemographic risk factors, as well as to estimate the coverage of myopia correction among adolescents in center of Portugal. Methods This cross-sectional study evaluated 1115 adolescents from the 5th to the 9th year of school, with an average of 12.9 years (SD = 1.5) ranging from 10.0 to 18.0 years. Optometric evaluations were carried out in a school environment and consisted of the evaluation of distance visual acuity, assessed using a logarithmic visual acuity chart (ETDRS charts 1 and 2) at 4 m, and measured by refractive error with a pediatric autorefractometer (Plusoptix), by non-cycloplegic. Myopia was defined as spherical equivalent (SE ≤ -0.50 diopter (D)) and uncorrected visual acuity (UVA ≤ 95VAR). Adjusted logistic regression analysis was applied to investigate risk factors. Results We found a myopia rate of 21.5% and a high myopia rate of 1.4%. Higher school level and attendance at urban schools were associated with myopia, but no association was found with age or sex. Only 34.6% of myopic adolescents use the best optical correction and 26.4% do not use any type of optical correction. Conclusions Data on the prevalence of refractive problems in Portugal are scarce and heterogeneous. This study, although regional, provides a valuable contribution with a clear and reproducible methodology, following international guidelines and filling gaps in the existing literature. The results show that the rate of myopia in this age group is similar to reports from other European studies. The high rate of adolescents with uncorrected or under-corrected myopia in Portugal is a problem that deserves attention.